Disfuncionalidades parentais: um caminho de conclusões erradas - Tinoco, Rui (2010)
In this article we make a reflection about the way that parental styles and practices can influence the interaction between children and their parents. Then we make a reflection about the impact of parental styles and the coherence between them, both on a longitudinal and transversal level. We think that the coherence is a crucial element in parental education. In the interaction between parents and their sons, several attributions and meanings can shift the relationship in a crucial way. Wrong attributions or labels are an example of this phenomenon. We systematize those kinds of interactions and the ways that they shape the children’s future. In conclusion, we underline some cares in clinical practice that contribute for the creation of an environment free of attributions and labels. We must defend for a space of acceptation and promotion of children´s development.